Anti-NGF does not change physical activity in normal young or aging mice but does increase activity in mice with skeletal pain - Majuta, Lisa A. (Pain, 2018)
Anti-NGF therapy has shown significant promise in attenuating several types of skeletal pain. However, whether anti-NGF therapy changes the level of physical activity in individuals with or without skeletal pain is largely unknown. Here, automated day/night activity boxes monitored the effects of anti-NGF treatment on physical activity in normal young (3 months old) and aging (18–23 months old) mice and mice with bone fracture pain. Although aging mice were clearly less active and showed loss of bone mass compared to young mice, anti-NGF treatment had no effect on any measure of day/night activity in either the young or aging mice. In contrast, in mice with femoral fracture pain, anti-NGF treatment produced a clear increase (10–27%) in horizontal activity, vertical rearing, and velocity of travel compared to the fracture + vehicle group. These results suggest just as in humans, mice titrate their level of physical activity to their level of skeletal pain. The level of skeletal pain may in part be determined by the level of free NGF which appears to rise following injury but not normal aging of the skeleton. In terms of bone healing, animals that received anti-NGF showed an increase in the size of calcified callus but no increase in the number of displaced fractures or time to cortical union. As physical activity is the best non-drug treatment for many patients with skeletal pain, anti-NGF may be useful in reducing pain and promoting activity in these patients.